The Widening of European Union to Post Soviet Countries: Case Study of Bulgaria Acceptance and Ukraine Accession - Eska Dwipayana Pulungan (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
To be a part of European Union must follow complex procedures. Before joining the institution, candidate countries must meet the Copenhagen Criteria. Then fulfill membership obligations contained in Acquis Communautaire. Once fulfilled, candidate countries can join the institution. However, in contrast to Bulgaria, Bulgaria was unable to fulfill it, but was given the easiness by providing CVM assistance. Bulgaria's acceptance was considered violate the EU agreement, making several members disappointed, especially UK. The peak of UK disappointment occurred in 2016, the UK stated its exit from the EU. Then in 2022, Ukraine in the midst of the Russian invasion applying to join. Without an in-depth administrative review, EU agreed to immediately grant candidate State status. Necessarily, a country which is applying EU, First should be on the waiting list with the status of a potential candidate countries and then second go to next status as a candidate countries, the last is recognize as a member of union. But Ukraine directly jump up to second status.